Donor Gamma-Glutamyl Transferase Is Associated With Liver Allograft Discard and Failure. (June 2021) - Zhang, Theodore; Hickner, Brian; Cotton, Ronald; Nguyen Galvan, Nhu Thao; Vierling, John M; O'Mahony, Christine; Goss, John A; Rana, Abbas
Introduction: The disparity between the number of individuals on the wait list and available liver allografts creates the need for a system that maximizes donor liver utilization and predicts graft failure. Research Question: This study aimed to determine the relationship between donor Gamma-Glutamyl Transferase (GGT), liver discard, and graft failure. Design: Through multivariate analysis from 53 966 deceased liver donors, we adjusted for donor clinical and demographic characteristics and compared donor GGT with allograft discard. We compared donor GGT ranges with graft failure and analyzed data from 47 269 liver recipients. Results: After adjusting for other factors, donor GGT was significantly associated with liver discard, with GGT over 200 U/L being most significant (OR 2.74, CI 2.51-2.99). Donor GGT under 20 U/L was also found to be a protective factor for post-transplant graft failure (HR 0.91, CI 0.83 – 1.00). Conclusion: Going forward, GGT should be included among other characteristics associated with allograft discard considered during the procurement process.